2021
DOI: 10.5935/1518-0557.20200089
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist in association with hCG versus hCG alone for final oocyte maturation triggering in GnRH antagonist cycles

Abstract: Objective: To analyze gonadotropin-releasing hormone (GnRH) agonist in association with human chorionic gonadotropin (hCG) (dual triggering) versus hCG alone (conventional triggering) for final oocyte maturation triggering in GnRH antagonist cycles in an unselected population of Brazilian women. Methods: This prospective case-control study involved 114 patients referred to autologous in vitro fertilization treatment between February 2018 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Their study also showed that the fertilization rate was similar between dual trigger and hCG protocol (mean±SD: 58±24 and 53±35, respectively; p =0.120) ( Ben-Haroush et al ., 2020 ). Similar results were shown recently by Oliveira et al . (2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Their study also showed that the fertilization rate was similar between dual trigger and hCG protocol (mean±SD: 58±24 and 53±35, respectively; p =0.120) ( Ben-Haroush et al ., 2020 ). Similar results were shown recently by Oliveira et al . (2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies proved its efficacy in inducing oocyte maturation ( Haas et al ., 2016 ; Oliveira et al ., 2016 ; Elias et al ., 2017 ; Zhang et al ., 2017 ; Ali et al ., 2020 ; Ben-Haroush et al ., 2020 ; Kim et al ., 2020 ), number of retrieved oocytes ( Haas et al ., 2016 ; Oliveira et al ., 2016 ; Fabris et al ., 2017 ; Zhang et al ., 2017 ), fertilized oocytes ( Oliveira et al ., 2016 ; Elias et al ., 2017 ; Lin et al ., 2019 ; Albeitawi et al ., 2022 ), implantation rate ( Oliveira et al ., 2016 ), clinical pregnancy rates ( Elias et al ., 2017 ; Fabris et al ., 2017 ; Lin et al ., 2019 ; Chern et al ., 2020 ) and live birth rates ( Oliveira et al ., 2016 ; Elias et al ., 2017 ; Lin et al ., 2019 ; Chern et al ., 2020 ; Hu et al ., 2021 ). On the other hand, several studies have shown that dual trigger of oocyte final maturation did not improve or it was equivalent to conventional hCG triggering in terms of IVF outcome ( Ding et al ., 2017 ; Eser et al ., 2018 ; Oliveira et al ., 2021 ). Since there is conflicting evidence regarding de benefits of dual triggering protocol in human reproduction assisted techniques, we aimed to contribute with new data about the subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, some investigations have shown the bene ts of using a dual-trigger for nal oocyte maturation and better clinical outcomes [12][13][14], while others have reported comparable or even worse outcomes [15,37]. Lately, a well-designed RCT study by Haas et al reported a promising effect of dual trigger in normal responders [13].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several trials have studied the use of dual-trigger and demonstrated lower risk of OHSS and similar or better clinical outcomes compared to the hCG-only trigger [11][12][13][14]. In the general population, some studies suggested that the dual-trigger improved the oocyte maturation rate [13,14], while others denied this positive effect [15]. Haas et al performed a large RCT and the results showed that, for normal responders, the dual trigger increased the number of oocytes, mature oocytes and number of blastocysts compared to the hCG-only trigger [13].…”
Section: Introductionmentioning
confidence: 99%